Development of a Single Detector Ring Micro Crystal Element Scanner: QuickPET II - Robert S. Miyaoka; Marie L. Janes; Kisung Lee; Byungki Park; Paul E. Kinahan; Tom K. Lewellen (Molecular Imaging)
This article describes a single ring version of the micro crystal element scanner (MiCES) and investigation of its spatial resolution imaging characteristics for mouse positron emission tomography (PET) imaging. This single ring version of the MiCES system, referred to as QuickPET II, consists of 18 MiCE detector modules mounted as a single ring in a vertical gantry. The system has a 5.76-cm transverse field of view and a 1.98-cm axial field of view. In addition to the scanner and data acquisition system, we have developed an iterative reconstruction that includes a model of the system's detector response function. Evaluation images of line sources and mice have been acquired. Using filtered backprojection, the resolution for a reconstructed line source has been measured at 1.2 mm full width at half maximum. F-18-2-fluoro-2-deoxyglucose mouse PET images are provided. The result shows that QuickPET II has the imaging characteristics to support high-resolution, static mouse PET studies using 18-F labeled compounds.